Online final examination: Managing academic integrity issues - Abdul Mutalip, Zaiton; Abdul Rahim, Hazli Rafis; Mohd Isira, Ahmad Sadhiqin; Amir Mohamed, Kamarul; Rihawi, Zeina (Semarak Ilmu Publishing, 2023)
Along with the COVID-19 pandemic, higher education has undergone significant changes, including the adoption of online emergency remote teaching and learning. Academicians are facing the issue of developing e-courses and finding appropriate techniques to assess students learning in an online setting while at the same time preserving academic honesty. Academic honesty is extremely critical in higher education. The core principles of academic integrity's are to protect a university's reputation and produce a better attitude of the graduates. Therefore, this paper summarizes methods used in minimizing academic dishonesty at the Fakulti Kejuruteraan Elektronik dan Kejuruteraan Komputer, Universiti Teknikal Malaysia Melaka, which focuses on an online final examination. The programme outcomes attainment of physical and online assessments is also compared and discussed. As students’ attitude and integrity utmost everything, fair and preventive approaches are then outlined.